Harmonizing Teaching Practices: An Evaluation of Lecturer Performance in Guitar Ensemble Instruction Using The Charlotte Danielson Framework - Tampatonda, Fery Virgiawan; Satyawati, Sophia Tri; Wasitohadi , Wasitohadi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to evaluate the performance of lecturers teaching the Guitar Ensemble course in the Music Study Program, Satya Wacana Christian University, using the Charlotte Danielson Model. The focus of this study is to identify areas that require improvement to enhance the quality of learning. Adopting an evaluative mixed-methods design, this research applies the Danielson Framework for Teaching, which classifies instructional practice into four domains: planning and preparation, classroom environment, instruction, and professional responsibilities. Data were collected through observation, semi-structured interviews, documentation, and questionnaires based on the model’s indicators. Quantitative data were analyzed descriptively using percentages, while qualitative data were examined using an interactive model, involving data reduction, display, and conclusion drawing. Findings show that overall lecturer performance is categorized as 'good'. The evaluation domains effectively capture important critical aspects such as subject mastery and communication skills. However, several areas require attention: the use of broader academic references, improved classroom management in ensemble practice, and the implementation of more participatory teaching strategies. While lecturers’ professional responsibilities were generally positive, the documentation of teaching journals remains insufficient. It is recommended that lecturers improve lesson planning and adopt interactive approaches such as reflective discussions and collaborative projects. Additionally, higher education institutions should support this process by enhancing facilities and providing ongoing professional development. These efforts are essential to ensure sustainable improvements in the quality of teaching and learning, particularly in music education settings where interaction, creativity, and collaboration are central.